Study on the gjb3 and gjb6 gene mutations among Malays with nonsyndromic hearing loss - Daud, Mohd Khairi Md; Rahman, Normastura Abd; Zainuddin, Zafarina (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2009)
Hearing loss is the most common sensory disorder in human. Previous journals reported that GJB2 gene is the most important gene involved in non-syndromic hearing loss; and GJB6 gene is the second most which contributed to. This study is to screen mutations in GJB2 and GJB6 gene among Malay patients with non-syndromic hearing loss. Ninety one patients and equal number of normal hearing subjects were recruited for this study after getting informed consent. DNA samples were collected using sterile buccal swab. After DNA extraction, genomic DNA was amplified then screened using dHPLC technique. Certain samples were sequenced to confirm the type of mutation. The result showed that only a few samples having mutations in GJB2 gene, while no sample having mutation of GJB6 gene.